2021
DOI: 10.1126/sciadv.abf4304
|View full text |Cite
|
Sign up to set email alerts
|

Genomic gain of RRS1 promotes hepatocellular carcinoma through reducing the RPL11-MDM2-p53 signaling

Abstract: Hepatocellular carcinomas (HCCs) are characterized by frequent somatic genomic copy number alterations (CNAs), with most of them biologically unexplored. Here, we performed integrative analyses combining CNAs with the transcriptomic data to reveal the cis- and trans-effects of CNAs in HCC. We identified recurrent genomic gains of chromosome 8q, which exhibit strong trans-effects and are broadly associated with ribosome biogenesis activity. Furthermore, 8q gain–driven overexpression of ribosome biogenesis regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 59 publications
2
26
0
Order By: Relevance
“…In contrast, EXOSC8 knockdown in p53 -/-CRC cells unchanged the binding of endogenous RPL5/11 to Mdm2, which is consistent with the previous report that p53 is necessary for the initial release of RPs from the nucleolus upon rRNA synthesis inhibition [18]. Intriguingly, other rRNA metabolism-related genes have also been reported to be involved in RPs-Mdm2-p53 ribosomal stress, including CNV gain-related overexpressed gene in tumors [29,33]. These results further highlight that the rRNA metabolism-related genes play important roles in ribosome biogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, EXOSC8 knockdown in p53 -/-CRC cells unchanged the binding of endogenous RPL5/11 to Mdm2, which is consistent with the previous report that p53 is necessary for the initial release of RPs from the nucleolus upon rRNA synthesis inhibition [18]. Intriguingly, other rRNA metabolism-related genes have also been reported to be involved in RPs-Mdm2-p53 ribosomal stress, including CNV gain-related overexpressed gene in tumors [29,33]. These results further highlight that the rRNA metabolism-related genes play important roles in ribosome biogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…The dissociation of RPL11 from the ribosomal complex allows it to bind to c-Myc and inhibit its transactivation ( 41 ). There is also evidence that RRS1 knockout inhibits the nuclear export of RPL11 and increases its accumulation in the nucleus ( 30 ). Consistent with these previous observations, the present study found that RRS1 knockdown significantly enhanced the interaction between RPL11 and c-Myc ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Increased ribosome biosynthesis is a prerequisite for sustaining the high proliferation rates of tumor cells ( 54 , 55 ). RRS1 is a regulator of ribosome biosynthesis and shows high expression levels in multiple tumors ( 14 , 24 - 28 , 30 ). Likewise, the present study also detected significantly higher levels of RRS1 in the breast cancer cell lines compared to normal breast epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes located in 3p23 and 8q13 were rearranged, indicating that the distal loss and/or gain of 8q may contribute to the pathogenesis of Caroli disease. Genomic gains of 8q can promote ribosome biogenesis activity, which promotes hepatocellular carcinoma development [ 41 , 42 ]. CC has a higher risk of malignancy transformation [ 43 , 44 , 45 ], although a link between chromosomal translocation t(3;8) leading to a gain of 8q13-qter and the risk of malignancy transformation in CC has yet to be established.…”
Section: Introductionmentioning
confidence: 99%